Pengaruh Disiplin Kerja Dan Kesehatan Keselamatan Kerja (K3) Terhadap Kinerja Karyawan SPBU Shell Satrio Jakarta Selatan - Rifki Haikal; Liawati Liawati (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Abstract. The purpose of this study is to determine the effect of Work Discipline and Occupational Health and Safety on employee performance and to determine the simultaneous effect of the variables of Work Discipline and Occupational Health and Safety on employee performance at the Shell Satrio gas station in South Jakarta. The sample used was a saturated sample of 56 employees. Data collection techniques included primary and secondary data. Data analysis techniques used descriptive statistics, validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, t-tests, and f-tests. The results of the study show that : (1) Partially, there is an influence between Work Discipline and employee performance at the Shell Satrio gas station in South Jakarta, which can be proven from the simple linear regression equation Y = 2.443 + 0.878 X1 and the t-value of 16.875> t-table 2.004 with a significance of 0.000 < 0.005. (2) Partially, there is an effect of Occupational Health and Safety on employee performance at the Shell Satrio gas station in South Jakarta, which can be proven from the simple linear regression equation Y = 4.408 + 0.827 X2 and a t-value of 13.696 > t-table 2.004 with significance 0.000 < 0.005. (3) Simultaneously, there is an influence between Work Discipline and Occupational Health and Safety on employee performance at the Shell Satrio gas station in South Jakarta, which can be proven from the multiple linear regression equation Y = 2.200 + 0.726 X1 + 0.159 X2, a correlation value of 0.920, a coefficient of determination value of 84.6%, and a calculated f value of 145.173 > f table 3.172 with a significance level of 0.000 < 0.005..